Inovasi dalam Perjalanan Umroh dengan Aplikasi Digital: Strategi Manajemen Risiko pada Aplikasi Muslim Pergi: Innovation in Umrah Travel with Digital Apps: Risk Management Strategy on Muslim Go App - Hasan; Thayib (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The transformation of religious tourism, particularly Umrah, has been significantly influenced by digital innovation. The Muslim Pergi application emerges as a technological breakthrough designed to facilitate Umrah travel services that are sharia-compliant, fast, and reliable. This study aims to analyze the innovation model of the Muslim Pergi application and its risk management strategy in the digital Umrah ecosystem. Using a descriptive qualitative approach through library research, this article explores academic journals, government regulations, and credible digital sources to identify risks and the mitigation strategies applied by the platform. The findings show that Muslim Pergi integrates multiple features such as online Umrah booking, group management, real-time worship guidance, and digital customer support. However, these innovations are not without challenges. The application faces various digital risks including data security breaches, system downtime, partner unreliability, transaction errors, and reputational threats. To address these, Muslim Pergi implements a combination of digital risk control, customer service optimization, and strict compliance with Indonesia’s Ministry of Religious Affairs regulations, particularly the Regulation of the Minister of Religious Affairs No. 5 of 2021. The study concludes that effective digital risk management is essential to sustain customer trust and service quality in the digital Umrah industry. This article contributes to the development of Islamic digital services by presenting a conceptual model that combines technological innovation with Islamic values and regulatory compliance. It is expected to serve as a reference for Islamic travel technology developers, policymakers, and researchers in Islamic digital innovation and risk governance.